VARIANTS OF GEOCULTURAL NARRATION (MUSEALISATION PRACTICES – POSTMONARCHICAL PATTERNS OF SPEECH) - Farago, Kornélia (Porównania, 2012)
The possibilities of geocultural narratology should be considered between research trends which strengthen fictional conceptions. Such trends enable looking at culture mostly by means of spatial terminology but thanks to that questions on the historical location can be formulated but also the attention can be focused on the time dimensions of the ‘geo’ part in culture. It is a principal question on the particular attributes which signalize, even in spite of the narrational differentiation in languages and ethnicity, that they belong to the same cultural space and that their “points of view are mutual” and that only in them the divideddividing traces of the repeatedly updating system are signalized. The analyses of places in the poetics of prose within geocultural narratology are linked with the interpretations of relations: with the space, area, surrounding, territory, border; they investigate the separation of places from culture which are different manipulations of the notions of stability instead of changeability, the idea of “never-ceasing transformation”, changing factors, the dislocated and nonfunctioning structure of being, the significance of objects, the paradox of experiencing the similarities that appear in the differences.